Emissão de gases de efeito estufa nos sistemas de colheita crua e queimada no estado de São Paulo, Brasil - Perillo, Luciano Ito [UNESP] (2014)
Sugarcane holds a prominent position in Brazilian economy and the recent changes occurred in the sector has been debated about the environmental impacts, specifically about greenhouse gas emissions. This work consisted of a greenhouse gas inventory due to the cultivation of sugarcane in São Paulo in the period 2006-2012, in which the main agricultural phases and emission sources involved were established. Also, the objective of this work was to evaluate the changes occurred in the cities of São Paulo state due the changes in the harvest system, from manual with previous burning to mechanize without burning. The results show that changing of the prevailing sugarcane management from burned to green harvested promoted a reduced growth of the emissions compared to the growth of the areas. The emission sources: synthetic N fertilizer, diesel, burning residues and liming represented, on average, 90% of the total emissions in São Paulo state. In the cities of São Paulo, the change of the harvest system promoted a decrease of the emissions per unit of productive area and the reduction of the emissions depends of the conversion rate and yield of the crop